Perioperative Outcomes Following Combined Versus Isolated Colorectal and Liver Resections - William H. Ward, MD, MS; Jane Hui, MD, MS; Catherine H. Davis, MD; Tianyu Li, MS; Neha Goel, MD; Elizabeth Handorf, PhD; Eric A. Ross, PhD, ScM; Steven A. Curley, MD; Andreas Karachristos, MD, PhD; Nestor F. Esnaola, MD, MPH, MBA (Annals of Surgery Open, 2021)
Objectives:. Our objective was to compare outcomes following combined versus isolated resections for metastatic colorectal cancer and/or liver metastases using a large, contemporary national database. Background:. Controversy persists regarding optimal timing of resections in patients with synchronous colorectal liver metastases. Methods:. We analyzed 11,814 patients with disseminated colorectal cancer and/or liver metastases who underwent isolated colon, rectal, or liver resections (CRs, RRs, or LRs) or combined colon/liver or rectal/liver resections (CCLRs or CRLRs) in the National Surgical Quality Improvement Program Participant Use File (2011–2015). We examined associations between resection type and outcomes using univariate/multivariate analyses and used propensity adjustment to account for nonrandom receipt of isolated versus combined resections. Results:. Two thousand four hundred thirty-seven (20.6%); 2108 (17.8%); and 6243 (52.8%) patients underwent isolated CR, RR, or LR; 557 (4.7%) and 469 (4.0%) underwent CCLR or CRLR. Three thousand three hundred ninety-five patients (28.7%) had serious complications (SCs). One hundred forty patients (1.2%) died, of which 113 (80.7%) were failure to rescue (FTR). One thousand three hundred eighty-six (11.7%) patients experienced unplanned readmission. After propensity adjustment and controlling for procedural complexity, wound class, and operation year, CCLR/CRLR was independently associated with increased risk of SC, as well as readmission (compared with LR). CCLR was also independently associated with increased risk of FTR and death (compared with LR). Conclusions:. Combined resection uniformly confers increased risk of SC and increased risk of mortality after CCLR; addition of colorectal to LR increases risk of readmission. Combined resections are less safe, and potentially more costly, than isolated resections. Effective strategies to prevent SC after combined resections are warranted.